A low-cost printed organic thermoelectric generator for low-temperature energy harvesting. (April 2021) - Shakeel, Muhammad; Rehman, Khalid; Ahmad, Salman; Amin, Mohsin; Iqbal, Nadeem; Khan, Arshad
Abstract: Global warming and pollution resulted from the increased power demand are some of the present era challenges associated with power generation through fossil fuels. To provide a solution, renewable energy systems are gaining much interest to capture energy through different energy harvesting devices. Among the energy harvesting devices, the thermoelectric generators (TEGs) are the ones with the ability to directly convert thermal energy into electrical energy without any environmental effects. However, their conventional fabrication methods are costly and possess environmental effects. This research reports an organic TEG fabricated through a cost-efficient and environmentally friendly process known as the direct ink write technique. The TEGs are printed onto a glass substrate, the most common insulator used in houses, and building windows with two different lengths. The active materials used are poly (3, 4-ethylene dioxythiophene) polystyrene sulfonate (PEDOT: PSS) ink which is an organic semiconducting material and silver ink. The maximum power outputs of 5.17 ± 0.5 nW and 4.08 ± 0.5 nW are recorded for TEGs with different characteristic lengths of 30 and 40 mm at a temperature gradient of 120 °C. Furthermore, the performance of TEG is also characterized for solar thermal energy harvesting. The results obtained are reasonably linear, stable, and comparable to previously reported. Highlights: TEGs are clean energy converters but their manufacturing is costly. Direct ink write technique shows a cost-efficient approach as compared to conventional technique. The technique have the capability of printing TEG directly on window glass for energy harvesting.